2002
DOI: 10.1056/nejmoa012407
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prognosis of Syncope

Abstract: Persons with cardiac syncope are at increased risk for death from any cause and cardiovascular events, and persons with syncope of unknown cause are at increased risk for death from any cause. Vasovagal syncope appears to have a benign prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
569
2
43

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,162 publications
(632 citation statements)
references
References 35 publications
18
569
2
43
Order By: Relevance
“…In comparison, based on this large observational study of 6128 patients treated with dapoxetine, it was observed that the incidence of syncope was zero, with the upper bound of the 95% confidence limit around 2.0 per 1000 person-years. One syncope case (alternative care/nondapoxetine) occurred in the context of 3315 patients (<0.1%) and was generally consistent with the literature reports of a background rate of vasovagal syncope of 1.31-6 per 1000 person-years [12] and 0.13% per patient [13].…”
Section: Discussionsupporting
confidence: 88%
“…In comparison, based on this large observational study of 6128 patients treated with dapoxetine, it was observed that the incidence of syncope was zero, with the upper bound of the 95% confidence limit around 2.0 per 1000 person-years. One syncope case (alternative care/nondapoxetine) occurred in the context of 3315 patients (<0.1%) and was generally consistent with the literature reports of a background rate of vasovagal syncope of 1.31-6 per 1000 person-years [12] and 0.13% per patient [13].…”
Section: Discussionsupporting
confidence: 88%
“…The age distribution of these patients visiting a general practitioner shows a peak in females around 15 years of age and a second peak in older patients (Fig. 4), a similar pattern to that observed in the general population [52,53]. A population-based study on the incidence of syncope in children and adolescents that sought medical attention in the USA showed a similar peak in 15-19 year old females [18].…”
Section: Studies In Health Care Settings ■ Syncope In General Practicesupporting
confidence: 66%
“…In the latest report of the Framingham Heart Study and the Framingham Offspring Study, syncope was defined differently from the first report, and included subjects with seizures, strokes and transient ischemic attacks (together 9 % of all syncopal episodes) [53]. Over a mean period of 17 years follow-up, 10 % of 7814 participants (mean age 51 years, range 20 to 96) reported at least one episode of syncope.…”
Section: ■ Framingham Studiesmentioning
confidence: 99%
“…In humans and dogs with various stages of different heart diseases, both syncope and decreased HRV are associated with increased risk of death 11, 19, 20, 25, 27, 28, 47, 48. Therefore, an association between a history of syncope and decreased HRV could be suspected.…”
Section: Discussionmentioning
confidence: 99%